European Expansion and the Contested Borderlands of Late Medieval Podillya, Ukraine - Mykhaylovskiy, Vitaliy (Beyond medieval Europe., 2019)
This book focuses on a key zone within the eastern frontier of medieval Europe: Podillya in modern-day Ukraine. Vitaliy Mykhaylovskiy offers a definitive guide to the region, which experienced great cultural and religious diversity, together with a continuous influx of newcomers. This is where Christian farmers met Muslim nomads. This is where German town residents and Polish nobles met urban Armenians and Tatars serving in the military. Podillya offers a unique opportunity to see interaction of so many peoples, principalities, and cultures - the eastern frontier of Europe at its most dynamic.